Implementation of an intersectoral program to eliminate human and canine rabies: the Bohol Rabies Prevention and Elimination Project. - Stella Marie D Lapiz; Mary Elizabeth G Miranda; Romulo G Garcia; Leonida I Daguro; Meydalyn D Paman; Frederick P Madrinan; Polizena A Rances; Deborah J Briggs (Public Library of Science (PLoS), 2012)
BACKGROUND: The province of Bohol, located in the Visayas islands region in the Philippines has a human population of 1.13 million and was the 4th highest region for human rabies deaths in the country, averaging 10 per year, prior to the initiation of the Bohol Rabies Prevention and Elimination Project (BRPEP). AIMS: The BRPEP was initiated in 2007 with the goal of building a sustainable program that would prevent human rabies by eliminating rabies at its source, in dogs, by 2010. This goal was in line with the Philippine National Rabies Program whose objective is to eliminate rabies by 2020. METHODS: The intersectoral BRPEP was launched in 2007 and integrated the expertise and resources from the sectors of agriculture, public health and safety, education, environment, legal affairs, interior and local government. The program included: increasing local community involvement; implementing dog population control; conducting mass dog vaccination; improving dog bite management; instituting veterinary quarantine; and improving diagnostic capability, surveillance and monitoring. Funding was secured from the national government, provincial, municipal and village units, dog owners, NGOs, the regional office of the WHO, the UBS Optimus Foundation, and the Global Alliance for Rabies Control. The BRPEP was managed by the Bohol Rabies Prevention and Eradication Council (BRPEC) under the jurisdiction of the Governor of Bohol. Parallel organizations were created at the municipal level and village level. Community volunteers facilitated the institution of the program. Dog population surveys were conducted to plan for sufficient resources to vaccinate the required 70% of the dogs living in the province. Two island-wide mass vaccination campaigns were conducted followed by "catch up" vaccination campaigns. Registration of dogs was implemented including a small fee that was rolled back into the program to maintain sustainability. Children were educated by introducing rabies prevention modules into all elementary schools in Bohol. Existing public health legislation at the national, provincial, and municipal level strengthened the enforcement of activities. A Knowledge, Attitude and Practices (KAP) survey was conducted in 2009 to evaluate the educational knowledge of the population. Increased surveillance was instituted to ensure that dogs traveling into and out of the province were vaccinated against rabies. Human and animal cases of rabies were reported to provincial and national authorities. KEY RESULTS: Within the first 18 months of the BRPEP, human rabies deaths had decreased annually from 0.77 to 0.37 to zero per 100,000 population from 2007-2009. Between October 2008 and November 2010 no human and animal cases were detected. Increased surveillance on the island detected one suspected human rabies case in November 2010 and one confirmed case of canine rabies in April 2011. Two mass vaccination campaigns conducted in 2007 and 2008 successfully registered and vaccinated 44% and 70% of the dogs on the island. The additional surveillance activities enabled a mobilization of mop up vaccination activities in the region where the human and canine case was located. Due to the increased effective and continuous surveillance activities, rabies was stopped before it could spread to other areas on the island. The program costs totaled USD 450,000. Registration fees collected to maintain the program amounted to USD 105,740 and were re-allocated back into the community to sustain the program.